2018
DOI: 10.1021/acs.jcim.7b00717
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Innate Immune Recognition of Opioid Inactive Isomer (+)-Naltrexone Derived Toll-like Receptor 4 (TLR4) Antagonists

Abstract: The opioid inactive isomer (+)-naltrexone is one of the rare Toll-like receptor 4 (TLR4) antagonists with good blood-brain barrier (BBB) permeability, which is a lead with promising potential for treating neuropathic pain and drug addiction. (+)-Naltrexone targets the lipopolysaccharides (LPS) binding pocket of myeloid differentiation protein 2 (MD-2) and blocks innate immune TLR4 signaling. However, the details of the molecular interactions of (+)-naltrexone and its derivatives with MD-2 are not fully underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 65 publications
1
40
0
Order By: Relevance
“…The primary structure characteristic results showed that the mean hydrophobicity index and the positive charge of LTP (−0.821, +5) were between those of LL-37 (−0.724, +0.6) and TP5 (−1.8, +1), which indicated that LTP had a more balanced positive charge and hydrophobicity than its parental peptides. These results suggested that LTP may have a stronger potential anti-inflammatory activity than its parental peptides based on previous studies [46,47].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The primary structure characteristic results showed that the mean hydrophobicity index and the positive charge of LTP (−0.821, +5) were between those of LL-37 (−0.724, +0.6) and TP5 (−1.8, +1), which indicated that LTP had a more balanced positive charge and hydrophobicity than its parental peptides. These results suggested that LTP may have a stronger potential anti-inflammatory activity than its parental peptides based on previous studies [46,47].…”
Section: Discussionsupporting
confidence: 69%
“…However, to our knowledge, scientific research is lacking on the rational design of peptide structures and the correlations between this type of information and anti-inflammatory activities. Based on previous findings, positive charge and hydrophobicity are required for a peptide to have anti-inflammatory activity, as these characteristics affect the LPS neutralization activity and cellular uptake ability of the peptides [46,47]. In the present study, we designed a hybrid peptide (LTP) by combining the active center of LL-37 (13–36) [34,35] with TP5.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, LAL depicted that CATH-2TP5 peptide binds to lipid A part of LPS and neutralizes the biological effects of endotoxin. However, based on previous reports, positive charge and hydrophobicity are essential for the peptide to have LPS neutralizing and anti-inflammatory characteristics (Sun and Shang, 2015;Zhang et al, 2018). In the current study, Our hybrid peptide comprises an N-terminal region along with polar active part of CATH-2 (16 amino acid) and a C-terminal TP5 having a net charge of +9 with reducing hydrophobicity as reported in the previous study (Gutsmann et al, 2010b;Kaconis et al, 2011;Ahmad et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Some glycolipid-based compounds, such as monosaccharidic FP7s and disaccharidic LAMs, can be effectively used systemically since they are water soluble and have a good distribution. On the other hand, highly hydrophobic non-glycolipid TLR4 antagonists, such as (+)-naltrexone, are better suited to target CNS diseases such as neuroinflammation, neuropathic pain, and neurodegenerative diseases including Alzheimer's disease (AD) ( 36 38 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Authors concluded that the binding of (+)-naltrexone and its derivatives to MD-2 are primarily driven by hydrophobic interactions. However, polar interactions, which includes both electrostatic interactions and polar solvation free energy, were negatively correlated with experimentally determined binding affinities ( 41 ).…”
Section: Non-glycolipid Tlr4 Modulatorsmentioning
confidence: 99%